Suitability of Ti–Zr Alloy for Dental Implants: Tribocorrosion Investigation - Ampadi Ramachandran, Remya; Barão, Valentim A. R.; Matos, Adaías Oliveira; Cordeiro, Jairo Matozinho; Grandini, Carlos R. [UNESP]; Sukotjo, Cortino; Mathew, Mathew T. (Springer Nature, 2021)
The dental implant failures and clinical complications have been increasing, and there is considerable interest in using alternative materials to replace commercially pure titanium (cpTi). This study identifies the ideal composition of titanium–zirconium (Ti–Zr) alloys based on their tribocorrosion characteristics when exposed to a simulated oral environment. The study involved a tribocorrosion test under the free potential mode to collect tribological and electrochemical data. The metal cpTi is taken as the control group and Ti5Zr, Ti10Zr, Ti15Zr (wt%) as experimental groups where these alloys were manufactured from pure metals (purity 99%). Tribocorrosion tests were performed in a corrosion cell installed on a tribometer with a reciprocating ball-on-disk configuration. Open circuit potential (OCP) evaluations were performed on each sample, and electrochemical impedance spectroscopy (EIS) measurements were taken before and after the sliding period. The surface characteristics were observed through scanning electron microscopy and white light interferometry analyses. Results reveal that adding Zr at different wt% has significantly influenced the alloys' tribocorrosion behavior and surface characteristics. Adding a 5% Zr component with Ti (Ti5Zr) has superior corrosion and wear resistance behavior, while an increase in Zr composition from 5 to 10% has adversely affected the corrosion/wear resistance behavior. However, Ti15Zr shows good corrosive nature over Ti10Zr. In conclusion, Ti5Zr exhibits optimal tribocorrosion and surface features, representing its suitable Zr mass% to limit the complex degradation processes.
Keywords: Dental implants; Electrochemical impedance spectroscopy (EIS); Open circuit potential (OCP); Titanium; Tribocorrosion; Wear-corrosion resistance; Zirconium